Crystal of pyridinylphenyl compound and method for producing same
Crystalline pyridinylphenyl compounds with specific X-ray diffraction peaks form stable complexes with aldehydes, addressing the limitations of existing dry eye treatments by reducing inflammation and improving tear secretion and corneal health.
Patent Information
- Application Number
- JP2023519557
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-28
- Filing Date
- 2021-09-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-09-28
AI Technical Summary
Existing treatments for dry eye syndrome, such as eye drops containing small-molecule drugs, react with aldehydes in the body, causing inflammation and discomfort, and fail to effectively penetrate the cornea.
Development of crystalline forms of pyridinylphenyl compounds with specific X-ray diffraction peaks that form stable complexes with aldehydes, allowing for safe and effective delivery to the eye without causing discomfort.
The crystalline compounds effectively reduce aldehyde toxicity, reduce inflammation, and improve tear secretion and corneal health in dry eye models, demonstrating therapeutic efficacy without causing discomfort.
Smart Images

Figure 0007612850000034 
Figure 0007612850000035 
Figure 0007612850000036
Abstract
Description
[Technical field]
[0001] This application claims priority to:
[0002] CN202011044638.7, application date: September 28, 2020.
[0003] The present invention relates to crystals of pyridinylphenyl compounds and methods for their preparation, and further includes the use of said crystals in the manufacture of a medicament for treating related disorders. [Background technology]
[0004] Dry eye, also known as keratoconjunctivitis sicca, is a general term for various diseases that cause abnormal tear quality, quantity, or dynamics for some reason, resulting in decreased tear stability and associated eye discomfort (or) ocular surface tissue lesions. Specific symptoms of discomfort include eye irritation, visual disturbance, and tear film instability. Some of these syndromes are caused by inflammation of the ocular surface, leading to loss of lacrimal gland function. In addition, they are also associated with systemic autoimmunity.
[0005] Some toxic aldehydes, such as malondialdehyde (MDA) and 4-hydroxy-2-nonenal (4HNE), are produced by tissues and organs in the body or eyes through metabolic mechanisms, and these aldehydes react highly with proteins, carbohydrates, fats and DNA, resulting in chemical modifications of biomolecules, leading to the activation of inflammatory molecular regulators such as NF-kappaB, and promoting damage to different organs, which is one of the causes of dry eye syndrome. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has found that low molecular weight drugs can enter the inflammatory site of the eye in the form of eye drops, and undergo complexation reaction with aldehyde in the body, thereby reducing the toxicity of aldehyde, reducing inflammation, and achieving the effect of treating dry eye.The compound represented by formula (II) has good chemical stability, and one molecule of hydrate is crystal water, which is arranged in a dense crystalline form.The compound represented by formula (II) can fully complex active aldehyde molecules both in vivo and in vitro, and can penetrate well into the cornea, and can play an anti-inflammatory role in treating dry eye.After administering eye drops to animals, all eye drops of the compound represented by formula (II) at the highest concentration do not cause any discomfort to animals, and have the properties of safety and efficacy in potential drug development. [Means for solving the problem]
[0007] The present invention provides a type A crystal of the compound represented by formula (I), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 7.14±0.20°, 12.46±0.20°, and 18.87±0.20°.
[0008] [ka]
[0009] In some embodiments of the present invention, the A-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 7.14±0.20°, 12.46±0.20°, 15.99±0.20°, 17.06±0.20°, 18.87±0.20°, 20.25±0.20°, 21.41±0.20°, and 25.00±0.20°.
[0010] In some embodiments of the present invention, the Type A crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 7.14±0.20°, 10.11±0.20°, 12.46±0.20°, 14.35±0.20°, 15.99±0.20°, 17.06±0.20°, 18.87±0.20°, 20.25±0.20°, 21.41±0.20°, and 25.00±0.20°.
[0011] The present invention provides a type A crystal of the compound represented by formula (I), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 7.142±0.200°, 12.456±0.200°, and 18.868±0.200°.
[0012] [ka]
[0013] In some embodiments of the present invention, the A-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 7.142±0.200°, 12.456±0.200°, 15.993±0.200°, 17.057±0.200°, 18.868±0.200°, 20.249±0.200°, 21.413±0.200°, and 24.995±0.200°.
[0014] In some embodiments of the present invention, the A-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 7.142±0.200°, 12.456±0.200°, 14.347±0.200°, 15.993±0.200°, 17.057±0.200°, 18.868±0.200°, 20.249±0.200°, 21.413±0.200°, 24.995±0.200°, 25.897±0.200°, 29.566±0.200°, and 30.442±0.200°.
[0015] In some embodiments of the present invention, the Form A crystal has a powder X-ray diffraction spectrum having the following 2θ angles: 7.142°, 8.234°, 10.112°, 11.302°, 12.056°, 12.377°, 12.456°, 14.086°, 14.347°, 15.993°, 16.530°, 16.834°, 17.057°, 17.482°, 18.868°, 20.249°, 21.413°, 22.599°. , 22.721°, 23.750°, 23.941°, 24.191°, 24.763°, 24.995°, 25.897°, 27.931°, 29.566°, 30.442°, 31.373°, 31.582°, 32.162°, 32.936°, 33.830°, 34.537°, 34.774°, 35.312°, 36.107°, 36.401°, and 37.575°.
[0016] In some embodiments of the present invention, the XRPD spectrum of crystalline Form A is essentially as shown in FIG.
[0017] In some embodiments of the present invention, the XRPD spectrum analysis data of the A-type crystal is as shown in Table 1.
[0018] [Table 1-1]
[0019] [Table 1-2]
[0020] [Table 1-3]
[0021] In some embodiments of the present invention, the differential scanning calorimetry curve of the A-type crystals has the onset of one endothermic peak at 81.03±3.0° C., 113.62±3.0° C., and 151.37±3.0° C., respectively.
[0022] In some embodiments of the present invention, the DSC spectrum of the above-mentioned Form A crystals is essentially as shown in FIG.
[0023] In some embodiments of the present invention, the thermogravimetric analysis curve of the A-type crystals shows a weight loss of 2.046% at 96.01°C±3.0°C and a weight loss of 7.708% at 163.66°C±3.0°C.
[0024] In some embodiments of the present invention, the TGA spectrum of the Form A crystals is essentially as shown in FIG.
[0025] The present invention provides a compound represented by formula (II):
[0026] [ka]
[0027] The present invention provides a B-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 8.231±0.200°, 17.058±0.200°, and 18.955±0.200°.
[0028] In some embodiments of the present invention, the B-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 8.231±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, and 25.678±0.200°.
[0029] In some embodiments of the present invention, the B-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 8.231±0.200°, 12.068±0.200°, 16.505±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, 24.242±0.200°, and 25.678±0.200°.
[0030] In some embodiments of the present invention, the B-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 7.083±0.200°, 8.231±0.200°, 11.294±0.200°, 12.068±0.200°, 14.091±0.200°, 16.505±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, 24.242±0.200°, 25.678±0.200°, and 30.869±0.200°.
[0031] The present invention relates to a compound having an X-ray powder diffraction spectrum at the following 2θ angles: 8.231±0.200°, 17.058±0.200°, and / or 18.955±0.200°, and / or 7.083±0.200°, and / or 11.294±0.200°, and / or 12.068±0.200°, and / or 14.091±0.200°, and / or 14.806±0.200°, and / or 16.505±0.200°, and / or 18.202±0.200°, and / or 21.712±0.200°, and / or 22.182±0.200°, and / or 23.903±0.200°, and / or 24.2 The present invention provides a B-type crystal of a compound represented by formula (II), characterized by having characteristic diffraction peaks at 42±0.200°, and / or 24.653±0.200°, and / or 25.350±0.200°, and / or 25.678±0.200°, and / or 26.270±0.200°, and / or 27.001±0.200°, and / or 27.658±0.200°, and / or 29.052±0.200°, and / or 29.721±0.200°, and / or 30.869±0.200°, and / or 34.644±0.200°, and / or 35.009±0.200°.
[0032] In some embodiments of the present invention, the B-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 7.083°, 8.231°, 11.294°, 12.068°, 14.091°, 14.806°, 16.505°, 17.058°, 18.202°, 18.955°, 21.712°, 22.182°, 23.903°, 24.242°, 24.653°, 25.350°, 25.678°, 26.270°, 27.001°, 27.658°, 29.052°, 29.721°, 30.869°, 34.644°, and 35.009°.
[0033] In some embodiments of the present invention, the XRPD spectrum of the B-type crystals is essentially as shown in FIG.
[0034] In some embodiments of the present invention, the XRPD spectrum analysis data of the B-type crystals is as shown in Table 2.
[0035] [Table 2]
[0036] In some embodiments of the present invention, the differential scanning calorimetry curve of the B-type crystals has the onset of one endothermic peak at 101.7±3.0° C. and 158.7±3.0° C., respectively.
[0037] In some embodiments of the present invention, the DSC spectrum of the B-type crystals is essentially as shown in FIG.
[0038] In some embodiments of the present invention, the thermogravimetric analysis curve of the B-type crystals shows a weight loss of 5.477% at 120.00°C±3.0°C.
[0039] In some embodiments of the present invention, the TGA spectrum of the B-type crystals is essentially as shown in FIG.
[0040] The present invention provides a C-type crystal of the compound represented by formula (I), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 12.871±0.200°, 17.488±0.200°, and 19.079±0.200°.
[0041] [ka]
[0042] In some embodiments of the present invention, the C-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 12.871±0.200°, 17.488±0.200°, 18.403±0.200°, 19.079±0.200°, and 20.853±0.200°.
[0043] In some embodiments of the present invention, the C-type crystal has characteristic diffraction peaks in a powder X-ray diffraction spectrum at the following 2θ angles: 12.871±0.200°, 13.274±0.200°, 14.294±0.200°, 17.488±0.200°, 18.403±0.200°, 19.079±0.200°, 20.853±0.200°, and 21.468±0.200°.
[0044] In some embodiments of the present invention, the C-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 10.105±0.200°, 12.871±0.200°, 13.274±0.200°, 14.294±0.200°, 17.488±0.200°, 18.403±0.200°, 19.079±0.200°, 20.853±0.200°, 21.468±0.200°, 22.647±0.200°, 23.977±0.200°, and 24.409±0.200°.
[0045] In some embodiments of the present invention, the C-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 9.128°, 10.105°, 12.871°, 13.274°, 13.933°, 14.294°, 16.420°, 17.488°, 18.403°, 19.079°, 20.853°, 21.468°, 22.647°, 23.042°, 23.507°, 23.977°, 24.409°, 24.798°, 25.861°, 26.309°, 28.698°, 30.293°, and 37.464°.
[0046] In some embodiments of the present invention, the XRPD spectrum of the above-mentioned Form C crystals is essentially as shown in FIG.
[0047] In some embodiments of the present invention, the XRPD spectrum analysis data of the C-type crystal is as shown in Table 3.
[0048] [Table 3]
[0049] In some embodiments of the present invention, the differential scanning calorimetry curve of the C-type crystals has an onset of one endothermic peak at 157.36±3.0°C.
[0050] In some embodiments of the present invention, the DSC spectrum of the C-type crystals is essentially as shown in FIG.
[0051] In some embodiments of the present invention, the thermogravimetric analysis curve of the C-type crystals shows a weight loss of 1.589% at 120.00°C±3.0°C.
[0052] In some embodiments of the present invention, the TGA spectrum of the C-type crystals is essentially as shown in FIG.
[0053] The present invention also provides a compound represented by formula (III).
[0054] [ka]
[0055] Here, m is selected from 0 to 1, and is preferably 0, 0.25, 0.5 or 1.
[0056] In some embodiments of the present invention, the compound has a structure represented by formula (III-1).
[0057] [ka]
[0058] The present invention provides a D-type crystal of the compound represented by formula (III-1), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 6.600±0.200°, 17.775±0.200°, and 19.138±0.200°.
[0059] In some embodiments of the present invention, the D-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.600±0.200°, 13.178±0.200°, 17.775±0.200°, 19.138±0.200°, and 25.798±0.200°.
[0060] In some embodiments of the present invention, the D-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.600±0.200°, 13.178±0.200°, 17.303±0.200°, 17.775±0.200°, 18.667±0.200°, 19.138±0.200°, 21.245±0.200°, and 25.798±0.200°.
[0061] In some embodiments of the present invention, the D-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.600±0.200°, 11.004.200°, 13.178±0.200°, 15.521±0.200°, 16.592±0.200°, 17.303±0.200°, 17.775±0.200°, 18.667±0.200°, 19.138±0.200°, 21.245±0.200°, 25.798±0.200°, and 27.353±0.200°.
[0062] In some embodiments of the present invention, the D-type crystal has a powder X-ray diffraction spectrum at the following 2θ angles: 6.600°, 8.659°, 9.558°, 11.004°, 12.463°, 13.178°, 13.728°, 14.871°, 15.521°, 16.592°, 17.303°, 17.775°, 18.379°, 18.667°, 19.138°, It has characteristic diffraction peaks at 20.572°, 21.245°, 21.989°, 22.247°, 22.561°, 23.940°, 25.087°, 25.798°, 26.686°, 27.353°, 28.044°, 28.859°, 29.645°, 30.375°, 32.351°, 34.603°, 35.456°, and 39.550°.
[0063] In some embodiments of the present invention, the XRPD spectrum of the above-mentioned Form D crystal is essentially as shown in FIG.
[0064] In some embodiments of the present invention, the XRPD spectrum analysis data of the D-type crystal is as shown in Table 4.
[0065] [Table 4]
[0066] In some embodiments of the present invention, the differential scanning calorimetry curve of the D-type crystals has the onset of one endothermic peak at 116.98±3.0° C., 133.04±3.0° C., and 154.86±3.0° C., respectively.
[0067] In some embodiments of the present invention, the DSC spectrum of the above-mentioned D-type crystals is essentially as shown in FIG.
[0068] In some embodiments of the present invention, the thermogravimetric analysis curve of the D-type crystal shows a weight loss of 6.939% at 150.00°C±3.0°C.
[0069] In some embodiments of the present invention, the TGA spectrum of the above-mentioned Form D crystal is essentially as shown in FIG.
[0070] The present invention provides a compound represented by formula (IV):
[0071] [ka]
[0072] Here, n is selected from 0 to 1, and is preferably 0, 0.25, 0.5 or 1.
[0073] In some embodiments of the present invention, the compound has a structure represented by formula (IV-1).
[0074] [ka]
[0075] The present invention provides type E crystals of the compound represented by formula (IV-1), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 18.097±0.200°, 18.691±0.200°, and 20.693±0.200°.
[0076] In some embodiments of the present invention, the E-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 17.465±0.200°, 18.097±0.200°, 18.691±0.200°, 19.1790.200°, and 20.693±0.200°.
[0077] In some embodiments of the present invention, the E-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.675±0.200°, 16.119±0.200°, 17.465±0.200°, 18.097±0.200°, 18.691±0.200°, 19.179±0.200°, 20.693±0.200°, and 26.658±0.200°.
[0078] In some embodiments of the present invention, the E-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.675±0.200°, 8.741±0.200°, 11.391±0.200°, 13.762±0.200°, 16.119±0.200°, 17.465±0.200°, 18.097±0.200°, 18.691±0.200°, 19.179±0.200°, 20.693±0.200°, 23.386±0.200°, and 26.658±0.200°.
[0079] In some embodiments of the present invention, the E-form crystal has a powder X-ray diffraction spectrum at the following 2θ angles: 6.675°, 8.741°, 9.365°, 11.391°, 12.205°, 13.310°, 13.762°, 15.302°, 16.119°, 16.407°, 17.465°, 18.097°, 18.691°, 19.179°, 20.6 It has characteristic diffraction peaks at 93°, 21.329°, 21.860°, 22.674°, 23.386°, 24.819°, 25.311°, 25.757°, 26.658°, 26.980°, 29.110°, 29.540°, 30.536°, 31.639°, 33.068°, 33.972°, 36.724°, and 38.646°.
[0080] In some embodiments of the present invention, the XRPD spectrum of the above Form E crystals is essentially as shown in FIG.
[0081] In some embodiments of the present invention, the XRPD spectrum analysis data of the above-mentioned E-type crystal is as shown in Table 5.
[0082] [Table 5]
[0083] In some embodiments of the present invention, the differential scanning calorimetry curve of the E-type crystals has the onset of one endothermic peak at 106.62±3.0° C., 134.32±3.0° C., and 158.33±3.0° C., respectively.
[0084] In some embodiments of the present invention, the DSC spectrum of the E-type crystals is essentially as shown in FIG.
[0085] In some embodiments of the present invention, the thermogravimetric analysis curve of the E-type crystals shows a weight loss of 6.673% at 150.00°C±3.0°C.
[0086] In some embodiments of the present invention, the TGA spectrum of the above-mentioned Form E crystals is essentially as shown in FIG.
[0087] The present invention provides a compound represented by formula (V):
[0088] [ka]
[0089] The present invention provides an F-type crystal of a compound represented by formula (V), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 14.012±0.200°, 16.936±0.200°, and 17.424±0.200°.
[0090] In some embodiments of the present invention, the F-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 14.012±0.200°, 16.936±0.200°, 17.424±0.200°, 17.954±0.200°, and 22.043±0.200°.
[0091] In some embodiments of the present invention, the F-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 12.567±0.200°, 14.012±0.200°, 15.666±0.200°, 16.936±0.200°, 17.424±0.200°, 17.954±0.200°, 20.717±0.200°, and 22.043±0.200°.
[0092] In some embodiments of the present invention, the F-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.104±0.200°, 12.567±0.200°, 14.012±0.200°, 15.666±0.200°, 16.936±0.200°, 17.424±0.200°, 17.954±0.200°, 20.717±0.200°, 22.043±0.200°, and 25.436±0.200°.
[0093] In some embodiments of the present invention, the F-type crystal has characteristic diffraction peaks in the powder X-ray diffraction spectrum at the following 2θ angles: 6.104°, 9.825°, 12.567°, 14.012°, 15.666°, 16.936°, 17.424°, 17.954°, 19.298°, 20.717°, 21.106°, 22.043°, 25.436°, 26.230°, 26.94°, and 29.721°.
[0094] In some embodiments of the present invention, the XRPD spectrum of the above-mentioned Form F crystals is essentially as shown in FIG.
[0095] In some embodiments of the present invention, the XRPD spectrum analysis data of the F-type crystal is as shown in Table 6.
[0096] [Table 6]
[0097] In some embodiments of the present invention, the differential scanning calorimetry curve of the F-type crystals has the onset of one endothermic peak at 83.44±3.0° C. and 154.65±3.0° C., respectively.
[0098] In some embodiments of the present invention, the DSC spectrum of the F-type crystal is essentially as shown in FIG.
[0099] In some embodiments of the present invention, the thermogravimetric analysis curve of the F-type crystals shows a weight loss of 2.972% at 120.00°C±3.0°C.
[0100] In some embodiments of the present invention, the TGA spectrum of the F-type crystals is essentially as shown in FIG.
[0101] The present invention also provides the use of the above compound or Type A crystals, Type B crystals, Type C crystals, Type D crystals, Type E crystals or Type F crystals in the manufacture of a medicament for treating dry eye. [Brief description of the drawings]
[0102] [Figure 1] 1 is an XRPD spectrum of Cu-Kα radiation of the A-type crystal of the compound represented by formula (I). [Diagram 2] 1 shows DSC and TGA spectra of type A crystals of the compound represented by formula (I). [Diagram 3] 1 is an XRPD spectrum of Cu-Kα radiation of a B-type crystal of the compound represented by formula (I). [Figure 4] 1 is a DSC spectrum of type B crystals of the compound represented by formula (II). [Diagram 5] 1 is a TGA spectrum of type B crystals of the compound represented by formula (II). [Figure 6]1 is an XRPD spectrum of Cu-Kα radiation of a C-type crystal of the compound represented by formula (I). [Figure 7] 1 shows DSC and TGA spectra of type C crystals of the compound represented by formula (I). [Figure 8] 1 is an XRPD spectrum of Cu-Kα radiation of the D-type crystal of the compound represented by formula (III-1). [Figure 9] 1 shows DSC and TGA spectra of the D-type crystal of the compound represented by formula (III-1). [Figure 10] 1 is an XRPD spectrum of Cu-Kα radiation of E-type crystal of the compound represented by formula (IV-1). [Figure 11] 1 shows DSC and TGA spectra of E-type crystals of the compound represented by formula (IV-1). [Figure 12] 1 is an XRPD spectrum of Cu-Kα radiation of an F-type crystal of a compound represented by formula (V). [Figure 13] 1 shows DSC and TGA spectra of F-type crystals of the compound represented by formula (V). [Figure 14] FIG. 2 is a structural ellipsoid diagram of the B-type crystal of the compound represented by formula (II). [Figure 15] 1 is a nuclear magnetic spectrum of the D-type crystal of the compound represented by formula (III-1). [Figure 16] 1 is a nuclear magnetic spectrum of E-type crystals of the compound represented by formula (IV-1). [Figure 17] 1 shows tear secretion volume in mouse scopolamine dry eye model animals. [Figure 18] Corneal fluorescent staining in a mouse scopolamine dry eye model animal. [Figure 19] 1 shows tear secretion volume in a rat hyperosmolar dry eye model animal. [Figure 20] Corneal fluorescent staining in a rat hyperosmolar dry eye model animal. [Figure 21] 1 shows tear film breakup time in rat hyperosmolar dry eye model animals. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0103] [Definitions and Explanations] Unless otherwise stated, the following terms and phrases used herein have the following meanings: A particular phrase or term, unless specifically defined, should be understood to have its ordinary definition, not to be indefinite or unclear. When a trade name appears in this specification, it refers to the corresponding product or its active ingredient.
[0104] The intermediate compounds of the present invention can be prepared by various synthetic methods familiar to those skilled in the art, including the specific embodiments listed below, embodiments in combination with other chemical synthetic methods, and equivalent alternative methods familiar to those skilled in the art, and preferred embodiments include, but are not limited to, the examples of the present invention.
[0105] The chemical reactions of the specific embodiments of the present invention are completed in suitable solvents, which should be suitable for the chemical reactions of the present invention and the reagents and materials required therefor. In order to obtain the compounds of the present invention, those skilled in the art may need to modify or select synthetic steps or reaction schemes based on the existing embodiments.
[0106] The structure of the compound of the present invention can be confirmed by conventional methods known to those skilled in the art, and when the present invention relates to the absolute configuration of the compound, the absolute configuration can be confirmed by conventional technical means of those skilled in the art. For example, single crystal X-ray diffraction (SXRD), the cultured single crystal is collected by Bruker D8 venture diffractometer, the light source is CuKα radiation, the scanning method is φ / ω scanning, after collecting the relevant data, the absolute configuration can be confirmed by direct method (Shelxs97) crystal structure analysis.
[0107] The present invention will be described in detail below with reference to examples, but these examples do not limit the present invention in any way.
[0108] All solvents used in this invention are commercially available and may be used as is without further purification.
[0109] All solvents used in the present invention can be obtained from commercial sources. The invention uses the following abbreviations: DCM stands for dichloromethane, DMF stands for N,N-dimethylformamide, DMSO stands for dimethylsulfoxide, EtOH stands for ethanol, and MeOH stands for methanol.
[0110] [Technical effect] The crystals of the compound of the present invention have good stability and are easy to be made into medicine. Eye drops of the B-type crystals of the compound represented by formula (II) can show good therapeutic effects on dry eye model mice induced by scopolamine hydrobromide solution, mainly improving the tear secretion amount and corneal damage in the dry eye model mice. Eye drops of the B-type crystals of the compound represented by formula (II) can show good therapeutic effects on dry eye model mice induced by hypertonic sodium chloride solution, mainly improving the tear secretion amount, corneal damage and tear film breakup time in dry eye model rats.
[0111] The X-ray powder diffractometer (XRPD) method of the present invention Instrument model: Bruker D8 Advance X-ray diffractometer Measurement method: Approximately 10 mg of sample is used for XRPD detection. Detailed XRPD parameters are as follows: Light tube: Copper tube / K-Alpha1 (λ=1.5418Å) Voltage: 40 kilovolts (kV) Current: 40 milliamps (mA) Rotation speed: 15[r / min] Scanning range: 3~39.9978[°] Step width: 0.020428946300[°] Time / step(s): 0.12[s] Total time: 234.72 [s]
[0112] Differential Scanning Calorimeter (DSC) Method of the Present Invention Instrument model: DISCOVERY DSC-2500 Differential Scanning Calorimeter Measurement method: A sample (0.5 mg to 1 mg) is placed in a DSC aluminum crucible and the measurement is performed by heating the sample from room temperature to 250°C at a heating rate of 10°C / min under 50 mL / min N2 conditions.
[0113] The Thermogravimetric Analysis (TGA) Method of the Present Invention Instrument Model: DISCOVERY TGA 5500 Thermogravimetric Analyzer Measurement method: The sample (2-5 mg) is placed in a TGA platinum crucible and heated from room temperature to 300°C at a heating rate of 10°C / min under 25mL / min N2 conditions, or until the weight is reduced by 20%.
[0114] In order to make the present invention more clearly understandable, the present invention will be further described below with reference to specific embodiments, but the specific embodiments do not limit the present invention. EXAMPLES
[0115] Example 1: Preparation of B-type crystals of the compound represented by formula (II)
[0116] [ka]
[0117] Synthesis scheme:
[0118] [ka]
[0119] Step 1: Preparation of Compound 2 Compound 1 (30 g, 130.4 mmol, 1 eq), bis(pinacolato)diboron (66.23 g, 260.80 mmol, 2 eq), [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane complex (5.32 g, 6.52 mmol, 0.1 eq) and potassium acetate (25.60 g, 260.80 mmol, 2 eq) were added to toluene (500 mL), purged with nitrogen gas three times, and the reaction solution was stirred at 110 ° C for 15 hours. After completion of the reaction, the reaction solution was filtered through diatomaceous earth, the filtrate was concentrated, and the residue was purified by column chromatography (petroleum ether: ethyl acetate = 0 ~ 100: 6) to obtain compound 2.
[0120] 1 H NMR (400 MHz, CDCl3) δ 7.84 (d, J=8.0 Hz, 1H), 7.06 (s, 1H), 7.04 (d, J=8.0 Hz, 1H), 5.65 (brs, 2H), 3.87 (s, 3H), 1.35 (s, 12H).
[0121] Step 2: Preparation of compound 4 Compound 3 (100 g, 460.79 mmol, 1 eq) was dissolved in absolute ethanol (1 L), and then concentrated sulfuric acid (225.97 g, 2.30 mol, 122.81 mL, 5 eq) and anhydrous sodium sulfate Na2SO4 (65.45 g, 460.79 mmol, 46.75 mL, 1 eq) were added, and the reaction solution was stirred at 85°C for 48 hours to react. After the reaction was completed, the reaction solution was cooled to room temperature. A saturated aqueous solution of sodium bicarbonate (1 L) was added dropwise to the reaction solution, and a large amount of solid was formed. It was filtered, the cake was washed with water (500 mL), and the obtained solid was dried in vacuum to obtain compound 4.
[0122] 1 H NMR (400 MHz, CDCl3) δ 8.10 (d, J=1.8 Hz, 1H), 7.26 (s, 1H), 4.47 (q, J=7.1 Hz, 2H), 1.46 (t, J=7.2 Hz, 3H).
[0123] Step 3: Preparation of compound 5 Compound 4 (70.00 g, 285.63 mmol, 1 eq) was dissolved in tetrahydrofuran (1 L) and cooled to -78°C under the protection of nitrogen gas. Methyllithium (1.6 M, 892.59 mL, 5 eq) was slowly added dropwise to the reaction solution, and the reaction solution was stirred at -78°C for 3 hours. After completion of the reaction, water (100 mL) was slowly added dropwise to quench the reaction, and the temperature was raised to room temperature, and saturated aqueous ammonium chloride solution (500 mL) was added to dilute the mixture, and the mixture was extracted with ethyl acetate (500 mL x 3). The organic phases were combined, dried over anhydrous sodium sulfate, and concentrated under reduced pressure to obtain the crude product. The crude product was slurried with n-heptane (500 mL), filtered, and dried to obtain compound 5.
[0124] 1 H NMR (400 MHz, CDCl3) δ 7.86 (d, J=1.9 Hz, 1H), 6.98 (d, J=1.9 Hz, 1H), 4.57 (br s, 2H), 1.57 (s, 6H).
[0125] Step 4: Preparation of compound 6 Compound 5 (10 g, 43.27 mmol, 1 eq), compound 2 (23.98 g, 86.55 mmol, 2 eq), [1,1'-bis(diphenylphosphino)ferrocene]palladium(II) dichloride dichloromethane complex (1.77 g, 2.16 mmol, 0.05 eq), cesium carbonate (28.20 g, 86.55 mmol, 2 eq) were added to dioxane (300 mL) and water (75 mL), purged with nitrogen gas three times, and the reaction solution was stirred at 80 ° C for 5 hours. After the reaction was completed, the reaction solution was concentrated, and the residue was purified by column chromatography (petroleum ether: tetrahydrofuran = 0 ~ 100: 40) to obtain crude product compound 6. The crude product was heated to 80 ° C in tetrahydrofuran (4 mL / g), cooled and recrystallized, stirred at 25 ° C for 15 hours, filtered, and the cake was dried to obtain compound 6.
[0126] 1H NMR (400 MHz, DMSO-d6) δ 7.94 (d, J=2.0 Hz, 1H), 7.77 (d, J=8.0 Hz, 1H), 7.17 (d, J=2.0 Hz, 1H), 6.99 (d, J=1.6 Hz, 1H), 7.77 - 7.75 (m, 3H), 5.69 (s, 2H), 5.50 (s, 1H), 3.81 (s, 3H), 1.52 (s, 6H).
[0127] Step 5: Preparation of Compounds of Formula (I) Compound 6 (8.78 g, 29.14 mmol, 1 eq) was dissolved in tetrahydrofuran (80 mL) and cooled to 0° C. under the protection of nitrogen gas. Methylmagnesium bromide (3 M, 97.12 mL, 10 eq) was added dropwise to the reaction solution and stirred at 0° C. for 1 hour. After completion of the reaction, saturated aqueous ammonium chloride solution (400 mL) was slowly added to quench the reaction, and the reaction was extracted with ethyl acetate (400 mL×2), the organic phase was concentrated under reduced pressure, and the residue, i.e., the crude product, was purified with dichloromethane (3 mL / g) at 25° C., filtered, and dried to obtain the product.
[0128] 1 H NMR (400 MHz, DMSO-d6) δ 7.88 (d, J=1.8 Hz, 1H), 7.15 - 7.01 (m, 2H), 6.82 (d, J=1.6 Hz, 1H), 6.69 (dd, J=1.5, 8.0 Hz, 1H), 5.59 (br s, 2H), 5.51 (br s, 2H), 5.44 (s, 1H), 5.23 (s, 1H), 1.51 (d, J=3.6 Hz, 12H).
[0129] 11.9 g of the above product was weighed into a round bottom flask, 150 mL of methyl tert-butyl ether was added, the sample was placed at 50° C. and stirred for 12 hours, then cooled to 25° C. and stirred for 4 hours. The solid was filtered and dried, and was detected as type A crystal by XRPD.
[0130] Approximately 50 mg of A-type crystals were weighed and added to a 2.0 mL glass vial, and an appropriate amount of solvent or solvent mixture was added to form a suspension. After adding a magnet, the sample was placed on a magnetic heating stirrer (25°C / 50°C) and stirred for one week, and after centrifugation, the resulting solid sample was placed in a vacuum dryer at 40°C and dried overnight to obtain B-type crystals of the compound represented by formula (II).
[0131] [Table 7-1]
[0132] Example 2: Confirmation of the structure of the compound represented by formula (II)
[0133] [ka]
[0134] Single crystal cultivation process: Approximately 5 mg of B-type crystals of compound represented by formula (II) was taken and dissolved in 3 mL of dichloromethane / methanol (2:1) at room temperature. The sample solution was placed in a 4 mL semi-sealed sample vial and allowed to slowly evaporate at room temperature. Colorless and transparent crystals were obtained on the 5th day. The size of the crystals used for the diffraction experiment was 0.20 × 0.18 × 0.15 mm. 3 It was.
[0135] Single crystal diffraction instrument: Bruker D8 venture Measured compound information: Molecular formula: C 17 H 25 N3O3, crystal system: monoclinic, space group: C2 / c, unit cell parameters: a=20.6603(14)Å, b=15.6554(14)Å, c=21.0124(16)Å, β=90.01°, α=γ=90°, volume: V=6796.4(9)Å 3 Figure 14 shows the three-dimensional structure of the B-type crystal of the compound represented by formula (II). At the same time, the crystal structure of the single crystal was measured and confirmed to be the B-type crystal.
[0136] Example 3: Preparation of each crystal
[0137] [ka]
[0138] Approximately 50 mg of A-type crystals were weighed and added to a 2.0 mL glass vial, and an appropriate amount of methanol or ethanol was added to form a suspension. After adding a magnet, the sample was placed on a magnetic heating stirrer (50°C) and stirred for one week, and after centrifugation, the obtained solid sample was placed in a vacuum dryer at 40°C and dried overnight to obtain C-type crystals of the compound represented by formula (I).
[0139] [ka]
[0140] Approximately 50 mg of A-type crystals were weighed and added to a 2.0 mL glass vial, and an appropriate amount of ethyl acetate was added to form a suspension. After adding a magnet, the sample was placed on a magnetic heating stirrer (25°C / 50°C) and stirred for one week. After centrifugation, the obtained solid sample was placed in a vacuum dryer at 40°C and dried overnight to obtain D-type crystals of the compound represented by formula (III-1). The nuclear magnetic data is shown in Figure 15.
[0141] [ka]
[0142] Approximately 50 mg of A-type crystals were weighed and added to a 2.0 mL glass vial, and an appropriate amount of acetonitrile was added to form a suspension. After adding a magnet, the sample was placed on a magnetic heating stirrer (25°C / 50°C) and stirred for one week. After centrifugation, the obtained solid sample was placed in a vacuum dryer at 40°C and dried overnight to obtain E-type crystals of the compound represented by formula (IV-1). The nuclear magnetic data is shown in Figure 16.
[0143] [ka]
[0144] Approximately 50 mg of A-type crystals were weighed and added to a 2.0 mL glass vial, and an appropriate amount of dichloromethane was added to form a suspension. After adding a magnet, the sample was placed on a magnetic heating stirrer (25°C) and stirred for one week. After centrifuging, the resulting solid sample was placed in a vacuum dryer at 40°C and dried overnight to obtain F-type crystals of the compound represented by formula (V).
[0145] Example 4: Preliminary stability experiment of B-type crystal of the compound represented by formula (II) As the test sample, about 50 mg of the B-type crystals of the compound represented by formula (II) were accurately weighed, placed in a dry and clean glass vial, spread into a thin layer, and fully exposed to the test conditions of the influencing factors (40°C, 25°C / 92.5% RH, light exposure, light exposure control) and accelerated conditions (40°C / 75% RH and 60°C / 75% RH). Samples were analyzed on the 5th and 10th day for the 40°C, 25°C / 92.5% RH, light exposure, and light exposure control, and samples were analyzed on the 1st, 2nd, and 3rd month for the accelerated conditions.
[0146] [Table 7-2]
[0147] Experimental conclusion: The B-type crystals of the compound of formula (II) were left under the influence factor test conditions (40°C, 25°C / 92.5% RH, light exposure, and light exposure control) for 10 days, under the condition of 40°C for 1 month, and under the long-term accelerated conditions (40°C / 75% RH and 60°C / 75% RH) for 3 months, and the crystals were stable.
[0148] Example 5: Water activity competition experiment at 25°C between type B crystals of the compound represented by formula (II) and type C crystals of the compound represented by formula (I) Approximately 15 mg of the C-type crystals of the compound represented by formula (I) were weighed out and an appropriate amount of the solvent system was added to each at room temperature to form a saturated solution. If the state was clear, the compound was continued to be added until the solution was saturated. After filtering into a liquid vial using a 0.45 μm nylon needle filter, approximately equal amounts of the B-type crystals of the compound represented by formula (II) and the C-type crystals of the compound represented by formula (I) were added to the liquid vial to prepare a suspension. After adding a magnet, the above suspension sample was placed in a thermostatic mixer (25° C., 700 rpm) and shaken.
[0149] [Table 7-3]
[0150] Results: When the water activity was 0, the B-type crystals of the compound represented by formula (II) and the C-type crystals of the compound represented by formula (I) were obtained after suspension and slurrying for 5 days. However, with increasing water activity, all the crystals obtained after suspension and slurrying for 5 days were the B-type crystals of the compound represented by formula (II). In addition, when the products obtained at water activities of 0.9 and 1.0 were dried and characterized, they were almost the same. Therefore, the B-type crystals of the compound represented by formula (II) were more stable than the C-type crystals of the compound represented by formula (I).
[0151] Biological Test Data Example 1: Study on the effect of eye drops of B-type crystals of the compound of formula (II) on mouse dry eye model Purpose of the test: To investigate the therapeutic effect of eye drops of the B-type crystals of the compound represented by formula (II) on a dry eye model in C57BL / 6 mice, a scopolamine hydrobromide solution was subcutaneously injected into the lower leg to induce a dry eye model in C57BL / 6 mice.
[0152] Testing process: According to the amount of tear secretion, the animals were randomly divided equally into five groups, which were a negative control group (physiological saline), a model control group (solvent), a low concentration group (1 mg / mL) of the B-type crystals of the compound represented by formula (II), a medium concentration group (2.5 mg / mL), and a high concentration group (5 mg / mL), each of which contained eight animals, all female. The day of grouping was recorded as D0. After grouping, the animals in each group were modeled according to the experimental setting, eye drops were administered, corneal fluorescent staining evaluation was performed, and tear secretion was measured.
[0153] Test Results: The compound of formula (II) type B crystal solutions (1 mg / mL, 2.5 mg / mL, 5 mg / mL) all had good therapeutic effects on the mouse dry eye model induced by scopolamine hydrobromide solution, and mainly improved the tear secretion and corneal damage in the dry eye model mice. From the evaluation results of tear secretion (Table 7, Figure 17) and corneal fluorescent staining (Table 8, Figure 18), it was determined that the eye drops of the compound of formula (II) type B crystals had the highest therapeutic effect at a concentration of 5 mg / mL.
[0154] [Table 7-4]
[0155] [Table 8]
[0156] Test conclusion: The eye drops of the B-type crystals of the compound represented by formula (II) had good therapeutic effects on dry eye models in mice induced by scopolamine hydrobromide solution, and mainly improved tear secretion and corneal damage in the dry eye model mice.
[0157] Example 2: Study on the effect of type B crystal eye drops of the compound represented by formula (II) on a rat hyperosmolar dry eye model Corneal fluorescent staining evaluation and tear secretion volume were measured for 20 female SD rats that were eligible for adaptation observation, and animals with problematic corneal fluorescent staining abnormalities and large differences in tear secretion volume were excluded.
[0158] Using a pipette, 20μL of sodium chloride solution (osmolarity: 500mOsmol / L) was taken and dropped into the conjunctival sac of both eyes of the animals 5 times / day, 20μL / time, each time at an interval of about 2 hours for 28 days, and the eyelids of the animals were passively closed for about 90 seconds after dropping. On the 14th day of the modeling period, the animals were subjected to fluorescent staining evaluation of the cornea of both eyes and tear secretion measurement, and the data was compared with the basic data, and animals with significant differences in tear secretion of both eyes were selected and divided into groups. According to the average value of the tear secretion of both eyes of the animals, the animals were randomly divided equally into 4 groups, which were the model control group, the low concentration group of the B-type crystal of the compound represented by formula (II), and the high concentration group (1mg / mL, 5mg / mL), respectively, with 4 animals and 8 eyes in each group, and the day of grouping was recorded as D0.
[0159] The animals in each group were administered eye drops at 10 μL / eye / time, 4 times / day, at intervals of about 3 hours on D1 for a total of 14 days, and their body weights were measured once a week during the administration period. Approximately 30 minutes after the second administration on D7 and D14, the tear secretion volume of both eyes was measured, and approximately 30 minutes after the third administration on D7 and D14, corneal fluorescent staining evaluation was performed. After measuring the D14 index, the animals were euthanized by carbon dioxide inhalation.
[0160] Experimental results: as shown in Tables 9, 10 and Figures 19, 20, and 21.
[0161] [Table 9]
[0162] [Table 10]
[0163] Experimental conclusion: The eye drops of the B-type crystals of the compound represented by formula (II) had good therapeutic effects on the rat dry eye model induced by hypertonic sodium chloride solution, and mainly improved the tear secretion volume, corneal damage and tear film breakup time in the dry eye model rats.
Claims
1. A B-type crystal of the compound represented by formula (II), characterized in that the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 8.231±0.200°, 17.058±0.200°, and 18.955±0.200°. 【Chemistry 1】
2. The B-type crystal according to claim 1, wherein the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 8.231±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, and 25.678±0.200°.
3. The B-type crystal according to claim 2, wherein the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 8.231±0.200°, 12.068±0.200°, 16.505±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, 24.242±0.200°, and 25.678±0.200°.
4. The B-type crystal according to claim 3, wherein the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 7.083±0.200°, 8.231±0.200°, 11.294±0.200°, 12.068±0.200°, 14.091±0.200°, 16.505±0.200°, 17.058±0.200°, 18.955±0.200°, 21.712±0.200°, 24.242±0.200°, 25.678±0.200°, and 30.869±0.200°.
5. The B-type crystal according to claim 4, wherein the powder X-ray diffraction spectrum has characteristic diffraction peaks at the following 2θ angles: 7.083°, 8.231°, 11.294°, 12.068°, 14.091°, 14.806°, 16.505°, 17.058°, 18.202°, 18.955°, 21.712°, 22.182°, 23.903°, 24.242°, 24.653°, 25.350°, 25.678°, 26.270°, 27.001°, 27.658°, 29.052°, 29.721°, 30.869°, 34.644°, and 35.009°.
6. The XRPD spectrum is as shown in Table 2. The B-type crystal according to claim 5.
7. A differential scanning calorimetry curve has an onset of one endothermic peak at each of 101.7±3.0° C. and 158.7±3.0° C., or The B-type crystal according to any one of claims 1 to 6, wherein the thermogravimetric analysis curve shows a weight loss of 5.477% at 120.00°C ± 3.0°C.
8. A medicine for treating dry eye, comprising the B-type crystal according to any one of claims 1 to 7.
Citation Information
Patent Citations
Compound for use in retinal diseases
WO2020125659A1